Age-related changes in cochlear and brainstem auditory functions in Fischer 344 rats - Popelar, Jiri; Groh, Daniel; Pelánová, Jana; Canlon, Barbara; Syka, Josef (Neurobiology of aging, 2006)
Auditory function in Fischer 344 (F344) and Long Evans (LE) rats was monitored during their lifespan by evaluating hair cell loss, middle-ear compliance and the recording of otoacoustic emissions and auditory brainstem responses. The results revealed a faster deterioration of hearing function in F344 rats compared with LE rats, resulting in larger hearing threshold shifts, a decrease in the latency and amplitude of click-evoked auditory brainstem responses, diminution of the distortion product otoacoustic emissions and a decrease in middle-ear compliance. However, hair cell loss, observed only at the most basal and apical parts of the organ of Corti, was comparable in older individuals of both rat strains. The results suggest involvement of cochlear (stria vascularis) and extracochlear (middle-ear) pathological changes during ageing. Thus, F344 rats represent a complex mix of conductive hearing loss (with low-frequency threshold shift, declining parameters of the middle-ear admittance and asymmetric otoacoustic emissions) and sensorineural hearing loss (with a decrease in the amplitudes of auditory brainstem response and a high-frequency threshold shift).
Keywords: potkani inbrední F344; Auditory Threshold; Male; Aging; vláskové buňky; Hearing; Rats, Long-Evans; Cochlea; mužské pohlaví; Evoked Potentials, Auditory, Brain Stem; sluchový práh; krysa rodu Rattus; Animals; Hair Cells, Auditory; zvířata; sluchové testy; kochlea; Rats; stárnutí; sluch; Rats, Inbred F344; potkani Long-Evans; sluchové kmenové evokované potenciály; Hearing Tests